حقوق نسواں اور جديد چیلنجز:تحقیقی جائزہ: Women’s Rights and Modern Challenges: A Research Review - Muhammad Naeem; Dr Syed Asif Mahmood (International Research Journal of Arabic and Islamic Studies, 2024)
Islam is the only religion that has guided us in all walks of life. Islam is a complete religion. Islam has given women a place of honor and respect. The teachings of the Qur'an and hadith are very clear in this regard. Surah Al-Nisaa, Al-Ma'idah, Al-Noor and Khatbah Al-Hijjat al-Vida teach the honor and respect of women. Islam has not only made a woman valuable in every respect, mother, daughter, sister, and mother, but has also given her separate rights in every respect . Islam demolished the mountains of atrocities committed on Bint e Hawa during the time of ignorance and removed the obstacles that hindered the growth and progress of Bint e Hawa. But unfortunately, about a hundred years ago, when a loud slogan of free women and women's rights was raised in the West, whose intentions and objectives were evil. This slogan not only engulfed the west in its trap, but also made many of the people of pakistan proud of it. And then the effects of this movement are still visible to us today in "My disease, transgender act" and many other forms. The purpose of all these movements was to propagate indecency and to fulfill their intended objectives, that even if the passion was true, it was invalid due to the lack of the light of the divine. The purpose of this paper is to discuss only two issues. One is what rights Islam has given to women and the second is how we can face the modern challenges in terms of women's rights and what role we can play for our regeneration and the survival of Islamic society.